Sustainability related activities for electrical and computer engineering students - Pahwa, Anil; Kuhn, William B.; Miller, Ruth Douglas; Rys, Andrew (Kansas State University, 2011)
A shortage of students pursuing electrical and computer engineering, coupled with both the need for sustainability and the desire of today’s students, especially women, to involve themselves in work that benefits society, suggests that incorporating sustainability principles throughout the electrical and computer engineering curriculum can bolster enrollment, while producing a diverse group of engineers equipped to meet the growing needs of society. As a field that is traditionally presented in a mathematical and abstract manner, electrical and computer engineering education must transform itself. Voltage and current must be felt and visualized. Students must realize that their daily life – cell phones, video games, computers, cars, electricity – are grounded in electrical and computer engineering. Moreover, with growing concern for our planet, they should be made aware of the career opportunities in alternate energy and in the development of sustainable technologies. The main goals of this project, funded by the National Science Foundation, are to recruit and prepare the next generation of electrical and computer engineers to meet the growing needs in alternate energy and sustainability, while revising the ECE curriculum to aid in recruitment of future students needed for this new workforce. Specific activities of the project are • Integrate substantial sustainability concepts into required freshman courses. • Enhance the freshman laboratory experience by introducing hands-on experiments in renewable energy • Increase the percentage of renewal energy and sustainability concepts and design projects in upper level classes. • Integrate discussions and writing assignment of sustainability in Senior Seminar • Develop fixed and portable demonstration systems to show generation of electricity from solar and wind to students as well as to general public. • Create a web site for the project to showcase ECE’s role in our future and thereby recruit high school students who seek the opportunity to make a valued and lasting impact in society. The presentation will focus on details of implementing the above mentioned activities and their outcomes.
Keywords: Sustainability; Renewable Energy; Electrical engineering; College students; Computer enginnering; Curriculum